Model bisnis E-commerce Produk Pertanian (Studi kasus pada PT. Limakilo Maju Bersama petani) - Adystiana Yashinta (Jurnal Manajemen Bisnis Performa, 2017)
Limakilo is one of the e-commerce companies in Indonesia which offers shallot as main commodity. The Company markets its products by being a direct mediator between farmers and consumers. Limakilo is a men in the middle with social function, different from negative connotations of middleman brokers. Focus of this research is description of Limakilo's business model in 9 elements Business Model Canvas. The research used qualitative method with snowball sampling. The result indicate that customer segment of  Limakilo is segmented market. Value propotion are cheap product prices than traditional market in Jakarta due to supply chain cuts. Channel using indirect and direct channel. Customer relationships is a personal assistants to help and serve consumers, self service when ordering process. Revenue stream obtained from sale of onion, garlic, chilli, tomato, potatoes, and rice, and investation. Key Resources consist of platform and trello, human, offices, laptops, farming tools, and financial. Key activities include activities with assisted farmers and supplier, online and offline business activities. Key partnerships alliance with assited farmers, Indimira and KUDO, coopetition with Kanigoro, and supllier. Cost structure at full micro-funded farmers and companies. This business model generates efficiency but still need to provide improvement of their business activities too.